Health-Seeking Behavior of People in Five Sub-Districts in Karawang Regency - Iqbal Ainnun Azis; Nita Arisanti; Helni Mariani; Dwi Agustian; Wulan Mayasari; Budi Sujatmiko (Faculty of Medicine, Public Health, and Nursing, 2021)
Background: Health-seeking behavior is an individual’s action to maintain and improve their degree of health and/or search for treatment, and it is influenced by many factors. The objectives of this study were to identify the preferences and reasons of people to visit healthcare facilities.Methods: This study was a descriptive study, conducted on November 5th 2019 at five sub-districts in Karawang Regency. Data were collected from all respondents using a guided questionnaire by trained enumerators. The respondents who did not complete the questionnaire were excluded from this study. Data were analyzed using Microsoft Office Excel 2013 and presented in percentages.Results: Out of 430 subjects, 18.6% were male and 81.4% were female, who were mostly in the age range of ≥ 18 years (99.5%). The sub-district health community center (Puskesmas) was the healthcare facilities most frequently visited and most preferred (39.7% and 40.9%), followed by a private clinic (21.3% and 22.3%) and a midwife (18.1% and 17.9%). Additionally, accessibility, affordability of the treatment cost, and waiting time were the main factors that influence people’s decision in using the healthcare facilities.Conclusion: The sub-district health community center was the healthcare facilities most frequently visited and most preferred by respondents. Accessibility, cost affordability, and waiting time were the factors that influence people’s decision in using the healthcare facilities.